1999
DOI: 10.1034/j.1600-0501.1999.100506.x
|View full text |Cite
|
Sign up to set email alerts
|

The implant neck: smooth or provided with retention elements. A biomechanical approach.

Abstract: A combined three‐dimensional and axisymmetric finite element analysis was made of the effect upon the peak interfacial shear stress of providing an axially loaded mandibular dental implant with retention elements all the way up to the crest of the implant as opposed to a smooth neck. The effect of increased wall thickness of the implant and of using bi‐cortical fixation as opposed to unicortical fixation was also studied. Retention elements at the implant neck were found to bring about a major decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
173
2
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(191 citation statements)
references
References 0 publications
8
173
2
5
Order By: Relevance
“…In the present study, higher stress/strain concentration was observed for the microthread implants, which may be explained by the horizontal profile of the microthread [30]. However, in this study the thread design of both modeled implants with or without microthreads had the upper region of the implant with a smooth surface.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…In the present study, higher stress/strain concentration was observed for the microthread implants, which may be explained by the horizontal profile of the microthread [30]. However, in this study the thread design of both modeled implants with or without microthreads had the upper region of the implant with a smooth surface.…”
Section: Discussioncontrasting
confidence: 47%
“…In this study, the difference in the concentration observed between the microthread and smooth models may act as a bone stimulus [30], since the bone strength acts as a physiological limit. Local overloading in cortical bone occurs in compression when the maximum compressive principal stress exceeds 170-190 MPa in modulus, and in tension when the maximum tensile principal stress exceeds 100-130 MPa [28,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…82 These surfaces have in general been compared to the socalled machined or turned surfaces, with little emphasis being paid to the range of surface textures that might exist within a machined screw implant. For crestal bone, Hansson 83 compared implants with smooth necks to those with screw thread along the entire implant to bone contact surface. It was found that a major decrease in peak interfacial shear stresses occurred if the entire implant to bone contact had a screw thread.…”
Section: '[Insert Figure 7 About Here]'mentioning
confidence: 99%